Hubungan Tingkat Pendidikan, Pengetahuan dan Dukungan keluarga Ibu Hamil terhadap kunjungan Kelas Ibu hamil di Desa Kedaton Kecamatan Kedaton Peninjauan Raya Kabupaten OKU tahun 2023 - nurmalela, nurmalela; Afrika, Eka (NHM PRESS, 2023)
Pregnancy and childbirth are physiological things experienced by a woman, but pregnancy and childbirth are risk factors for maternal mortality and morbidity. Today's health development programs in Indonesia are still prioritized on efforts to improve the health status of mothers and children, especially for the most vulnerable to health, namely pregnant women, childbirth and babies in the perinatal period. In Indonesia in 2021 there were 7,389 maternal deaths, while in the Province of South Sumatra in 2020, the maternal mortality rate was 175 people. Considering the still high maternal mortality rate, the government is formulating efforts to provide and use Maternal and Child Health (MCH) books with this book expected to improve the quality of maternal and child health services. The purpose of this study was to determine the relationship between the level of education, knowledge and family support of pregnant women simultaneously for class visits of pregnant women in Kedaton Village, Kedaton Peninjauan Raya District, Ogan Komering Ulu Regency in 2023. The research design used was quantitative analytic research with a cross approach. sectional. The population in this study were all pregnant women in Kedaton Village, Kedaton Peninjauan Raya District, Ogan Komering Ulu Regency in 2023, totaling 40 pregnant women. The results of the univariate analysis of 40 respondents were 28 respondents (70.0%) with class visits of pregnant women who were good and who were not good, totaling 12 respondents (30.0%). The results of the chi-square statistical test for education level variable obtained ρ value = 0.004 , variable mother's knowledge ρ value = 0.000 and husband/family support variable ρ value = 0.000 less than α = 0.05 indicating there is a significant relationship between knowledge of pregnant women and class visits of pregnant women in Kedaton Village, Kedaton District Peninjauan Raya, Ogan Komering Regency Year 2023